A rare case of solitary unifocal Langerhans cell histiocytosis with orbital extension: Diagnostic dilemma - Addenan, Maftuhim; Choo, May May; Teoh, Kean Hooi; Ismail, Fazliana; Kamalden, Tengku Ain (Medknow Publications, 2018)
Langerhans cell histiocytosis (LCH) is rarely encountered in ophthalmology practice. It is a spectrum of disorder characterized by accumulation of histiocytes in various tissues. Diagnosis is challenging as it may simulate periorbital hematoma, rhabdomyosarcoma, and neuroblastoma. We report a case of unifocal LCH with orbital extension. Diagnosis was obtained from incisional biopsy, and histopathological examination showed numerous histiocytes with eosinophilic infiltrations. The presence of Langerhans cells was confirmed by the presence of protein S-100, CD1a, and/or Langerin (CD207). Treatment depends on the degree of organ involvement. She responded well to cytotoxic drugs and steroids. This emphasized that prompt tissue diagnosis is crucial for early management.